Thermal Effects of 940 nm Diode Laser on Dental Socket Blood after Teeth Extraction for Diabetic Patients - Noor A. Al-Wardi, Mohammed A. Al-Maliky and Ali S. Mahmood (Iraqi Journal of Laser, 2018)
Abstract: Background: High percentage of diabetes patients complain from post extraction hemorrhage. Many types of hemostatic materials are used to stop bleeding after teeth extraction: diode lasers are good hemostatic agents owing to their highly absorption by hemoglobin therefore they are used in soft tissue procedures with relatively no effects on dental hard tissues due to their poorly absorption by water and hydroxyapatite. Objectives: The aim of this study is to evaluate the efficiency of diode laser to assist the clot formation after tooth extraction for type II diabetes patients with minimum temperature elevation to prevent periodontal destruction. Materials and methods: From 12 type II diabetes patients (7 males and 5 females with age mean of 49.5) blood samples are obtained for the pilot study of clot formation and for studying the thermal effects of laser on blood, then the selected dose is applied on the extracted dental sockets of diabetes patients. Results: A significant difference is observed in the temperature of blood before and after laser application; the mean temperature elevation is less thanthe critical temperature of periodontal destruction. Moreover, firm blood clot is formed over the extraction site; the follow up of patients shows good healing with relatively no complications. Conclusions: Diode laser assists in the coagulation of the dental socket after tooth extraction without thermal damage to the periodontium.